The relation between fibrosis of hilar lymph glands and the development of parenchymal silicosis. Issue 4 (April 1991) - Murray, J; Webster, I; Reid, G; Kielkowski, D
Abstract : The necropsy findings on the cardiorespiratory organs of 849 South African gold miners were analysed to test the hypothesis that fibrosis of the hilar lymph glands predisposes to the development of parenchymal silicotic nodules. Four hundred and eighty three cases had fibrosed glands, 34% of which also had parenchymal silicosis. By comparison, of 238 cases with silicosis, 88% had fibrosed glands. The proportion of cases with both silicosis and fibrosed glands, as well as those with gland fibrosis only, increased with increasing duration of exposure. As far as can be ascertained from a necropsy series such as this, it is possible that fibrosis of the lymph glands may predispose to the development of lung parenchymal silicosis.